New definition of resistant starch types from the gut microbiota perspectives - a review - Li, Cheng; Hu, Yiming (Critical reviews in food science and nutrition, 2023)
Current definition of resistant starch (RS) types is largely based on their interactions with digestive enzymes from human upper gastrointestinal tract. However, this is frequently inadequate to reflect their effects on the gut microbiota, which is an important mechanism for RS to fulfill its function to improve human health. Distinct shifts of gut microbiota compositions and alterations of fermented metabolites could be resulted by the consumption of RS from the same type. This review summarized these defects from the current definitions of RS types, while more importantly proposed pioneering concepts for new definitions of RS types from the gut microbiota perspectives. New RS types considered the aspects of RS fermentation rate, fermentation end products, specificity toward gut microbiota and shifts of gut microbiota caused by the consumption of RS. These definitions were depending on the known outcomes from RS-gut microbiota interactions. The application of new RS types in understanding the complex RS-gut microbiota interactions and promoting human health should be focused in the future.